Effect of 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (dppe)-peg2000 and 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (dppe)-peg5000 on fatty acid nanoliposomes and their langmuir monolayer / Teo Yin Yin - Teo, Yin Yin (2012)
Liposome is an artificial colloidal particle that formed from convolution of bilayer structure from amphiphilic molecules into a spherical particle. At certain pH, the presence of both ionized and non-ionized fatty acid molecules in the solution leads to the formation of dimers that can be an analog to the double chain phospholipids. Fatty acid liposomes provide both hydrophilic and hydrophobic compartments that make them suitable candidates as a carrier for water soluble and liposoluble substances that have potential for medicinal or cosmetic applications. Unmodified fatty acid liposome suspensions are normally unstable and it needs to be addressed so that it is more viable for useful applications. The widely applied method in stabilizing of liposome is through steric stabilization. In this study, polyethoxylated groups with different polymerization degree grafted to phospholipids namely 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)2000] and 1,2-dipalmitoyl-snglycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)5000] were incorporated in fatty acid liposome to improve their stability. The stability of fatty acid/PEGylated lipid liposomes was characterized by their critical vesiculation concentration, mean particle size and zeta potential for a period of 30 days. The presence of liposomes was identified by transmission electron micrograph. It was found that the stability of fatty acid liposomes can be enhanced with incorporation of PEGylated lipid. Langmuir monolayer isotherm was used for the intermolecular interaction study, and the most compatible mixture proportion of fatty acid to PEGylated lipid for the formation of a stable liposome suspension was proposed accordingly. The energetically favorable composition of a resulting mixture was found varied slightly depending on the type of PEGylated lipid. The loading efficiencies of these liposomes were assessed by both water soluble calcein as well as water insoluble α-tocopherol acetate. Certain amount of these compounds could be successfully loaded into the resulting liposomes under this experimental condition. As for a fixed fatty acid concentration, the loading efficiency was found to be affected by the type of fatty acid, bilayer composition and the amount of calcein and α-tocopherol acetate.